Efektivitas Kebijakan Pemberian BLT di Desa Pulubala Kecamatan Pulubala Kabupaten Gorontalo - Putri Regina Pakaya; Zuchri Abdussamad; Irawaty Igirisa (Politeknik Kampar, 2024)
The research findings indicate that the effectiveness of the BLT policy in Pulubala Village, Pulubala Subdistrict, Gorontalo Regency as a whole assessed from the effectiveness indicators namely timeliness was still lacking. The certainty in the timing of the distribution of funds to the community was often hampered by the disbursement of funds from the center made the targeted people having difficulties to make ends meet. In terms of target appropriateness, there were still people who did not fit the criteria that were determined by the government to obtain this BLT assistance. The indicator of goal determination that the government and the village officials wanted to achieve for the distribution of funds to the community had been running optimally because the BLT-DD fund was used appropriately by the beneficiaries. However, target accuracy was still not optimal as a whole because it was less effective in term of selecting prospective beneficiaries, while other aspects was maximized, such as the purpose of distribution. Therefore, based on this analysis, it can be concluded that the effectiveness of the BLT policy in Pulubala Village, Pulubala Subdistrict, Gorontalo Regency was not optimal. In the future, it is expected that there will be more appropriate schedule and distribution of BLT to the beneficiaries, and no more nepotism in selecting prospective beneficiaries.